Penerapan Metode Questions Students Have dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Akidah Akhlak - Wahab, Abd.; Nurhayati, Sri (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the implementation of the Questions Students Have (QSH) method and its impact on increasing students’ learning interest in the subject of Aqidah and Akhlak. Low learning interest among students is often caused by teaching methods that do not actively engage them in the learning process. The QSH method encourages students’ participation and curiosity by providing opportunities to express questions that arise during learning activities. This research employed a qualitative descriptive approach, with data collected from principals, subject teachers, and students through interviews, observations, and documentation. The data were analyzed descriptively to identify patterns and impacts of the QSH method. The results show that (1) the QSH method is implemented by distributing question sheets, allowing students to formulate questions individually, followed by group discussions; and (2) the method effectively increases learning interest, as reflected in students’ enthusiasm, attentiveness, willingness to ask questions, and active participation in discussions. Therefore, the QSH method can serve as an effective pedagogical strategy to foster students’ engagement and motivation in Aqidah and Akhlak learning.